Fears and inhibitions in speaking during cross-cultural student exchange projects on the example of a student encounter between Berlin and Poznań - Schmidt-Bernhardt, Angela; Adamczak-Krysztofowicz, Sylwia; Storozenko, Victoria (Glottodidactica, 2022)
In this article, the authors concentrate on the manifestations of fears and speaking anxiety in multicultural student exchange projects. In the first part, numerous facets of speaking anxiety in different contexts are presented, including its potential causes and symptoms. The authors then proceed to discuss student encounters and student exchange projects in an intercultural context. In the empirical part, they present the initial results of the study on (not only) language anxiety experienced during a German-Polish student exchange between Poznań and Berlin in autumn 2018. Finally, some implications for dealing with speaking anxiety experienced in foreign language learning/teaching and during student exchange projects are suggested.